Epigraphy of art : ancient Greek vase-inscriptions and vase-paintings - Yatromanolakis, Dimitrios (Archaeopress archaeology., 2016)
Ancient Greek vase-paintings offer broad-ranging and unprecedented early perspectives on the often intricate interplay of images and texts. By bringing together, for the first time, an international group of leading scholars in classical art and archaeology who have worked on vase-inscriptions, this book investigates both epigraphic technicalities of Attic and non-Attic inscriptions, and their broader, iconographic and sociocultural, significance. The ten chapters in this book propose original and expert methodological approaches to the study of vase-inscriptions and vase-paintings, while also foregrounding the outstanding but not fully examined importance of the area of vase-inscriptions for current research on ancient Greek visual representations.